Relationship Of Characteristics With Mother's Actions In The Prevention Of Malaria In The Working Area Of The Hutabalang Puskesmas In 2020- A Cross-Sectional Study Of Tertiary Puskesmas In Sibolga - Syarul Khairiaty; Ayu Musda; Tetti Sianturi (Science Midwifery, 2020)
Malaria is an infectious disease that is a major public health problem in the world, including Indonesia. This study aims to determine the relationship between characteristics and maternal actions in preventing malaria in the Hutabalang Health Center Work Area. The research design used is descriptive analytic research. Total sampling is 60 respondents. The measuring instrument used is a research questionnaire. Data processing by editing, coding and tabulating. Data analysis using Chi Square Test. The results showed that there was an effect of age, knowledge and attitude on the mother's actions in preventing malaria. There is no influence of education and work on the mother's actions in preventing malaria. Suggestions for respondents to dig up more information about malaria prevention from various sources such as the internet, books and health workers.